Ataques de onça-parda sobre criações domésticas no oeste do Estado de São Paulo - Fuini, Gabriela Rigotti [UNESP] (2016)
The conflict between humans and wild carnivores due the predation on domestic livestock has been a reason that made the Carnivora one of the groups with most threatened species. In Brazil, predation by pumas has been recorded in various regions and result in a harsh persecution on these animals. In order to identify factors that might be associated with predation on domestic livestock by pumas in the west of São Paulo, we did interviews with farm owners and their regular employees using a semi structured questionnaire, addressing characteristics of the property, the management and landscape. We conducted 71 interviews and identified properties that had gone through predation events in the last decade. Sheep and cattle were the most often attacked species. Using logistic regression it was possible to obtain a predictive model of attacks with 81% agreement between estimated and observed, in which the number of sheep and amount of natural vegetation present in each property was positively related to cases of predation. However, a proper management of individuals under risk for both sheep and calves showed to be effective and can contribute significantly to reduce livestock losses and thus to reduce potential conflicts with wildlife.